THE EFFECT OF GUIDED INQUIRY LEARNING MODEL ON STUDENTS’ LEARNING OUTCOMES IN SCIENCE VIII CLASS JUNIOR HIGH SCHOOL - Sri Rahmiati; Hasanuddin Hasanuddin; Sitti Saenab (Universitas Negeri Makassar, 2024)
This study aims to determine (1) the science learning outcomes of students who taught with Mind Mapping Based Guided Inquiry Learning and direct instructions based on mind mapping (2) the influence of mind mapping based giuded inquiry learning model on learning outcomes. This research is a quasi experimental with posttest only control group design. The research population was all students of class VIII SMP Negeri 1 Makassar. The sample was selected by purposive sampling and obtained class VIII.1 as the control class and class VIII.1 as the experimetal class. The instruments was cognitive learning outcomes test in the form of 25 numbers multiple choice test. Data analysis technique are descriptive and inferential statistics. The results of the study were found: (1) the science learning outcomes of students who taught using the Mind Mapping Based Guided Inquiry Learning are in the high category with an average score of 19 and students who taught using the direct instructions based on mind mapping are in the high category with an average score of 15,8 (2) There is an effect of mind mapping based guided inquiry learning on student’s science learning outcomes students of class VIII SMP Negeri 1 Makassar.